Radiant star - Leckie, Ann (Orbit, 2026)
"The Temporal Location of the Radiant Star has always been a source of both conflict and hope for the people of Ooioiaa. However, the imperial Radch see it only as an inconvenience, an antiquated religious site soon to be absorbed into their own, superior culture. But local politics is complicated, and the Radch have made one last concession: One last man will be allowed to join the mummified bodies in the temporal location to become a "living saint". But this one decision will ripple out to affect every part of the city. Amidst a slowly worsening food shortage, riots, and a communication blackout from the rest of the Radch Empire, a religious savant will entertain visions of his own sainthood, a socialite will discover her comfortable life upended, and a young man sold into servitude will find unlikely escape"-- Provided by publisher.